Freezing of Upper Limbs in Parkinson's Disease: A Systematic Review. - Martins, Núbia Isabela Macêdo; Aguiar, Mariana Machado de; Correa, Clynton Lourenço (Physical & Occupational Therapy in Geriatrics, 2022)
To identify how FOUL is investigated in patients with PD. The Preferred Reporting Items for Systematic Reviews guideline was used, and the search was carried out in four databases, with no limit on publication date. 21 original articles were included. They used a variety of terms for upper-limb freezing. Some tasks evaluated only the movement of the limbs; others used associated objects. The tasks most often used to assess FOUL were flexion and extension of the index finger, finger tapping (index finger on thumb), and Funnel Task. In these tasks, movements of small amplitude/high frequency and the presence of a dual-task elicited more FOUL episodes. This review highlights the need for development and validation of FOUL detection and assessment in clinical practice. The use of an appropriate assessment will prevent false-negative results and allow the phenomenon to be identified and treated.